The efficacy and mechanism of acupuncture in the treatment of male infertility: A literature review - Feng, Jiaxing; He, Hui; Wang, Yu; Zhang, Xu; Zhang, Xiuying; Zhang, Tiantian; Zhu, Mengyi; Wu, Xiaoke; Zhang, Yuehui (Frontiers in Endocrinology, 2022)
Fertility, a social, cultural, and medical issue, has aroused public attention because of its potential to predict future health. In recent years, the incidence of male infertility has increased significantly, and various risk factors, such as congenital factors, acquired factors, and idiopathic factors, have led to this situation. Male infertility causes substantial psychological and social distress on patients. With the implementation of the two-child policy, male infertility has brought enormous psychological and social pressure and huge economic burden to patients and the health-care system. This has attracted the attention of not only men of childbearing age, but also many male experts. The conventional therapeutic approaches for treating male infertility, including drugs, varicocele surgery, intrauterine insemination, in vitro fertilization and intracytoplasmic sperm injection, can restore fertility to a certain extent, but their efficacy is far from satisfactory, not to mention some adverse events. Therefore, acupuncture has been chosen by many males to treat their infertility and produced significant effects. In present paper, the efficacy and mechanism of acupuncture in the treatment of male infertility were analyzed from different perspectives such as regulating hormone secretion, reducing inflammation, improving semen parameters, etc. The existing literature shows that acupuncture can effectively treat male infertility.